The machine that changed the world : the story of lean production : how Japan's secret weapon in the global auto wars will revolutionize western industry - Womack, James P.; Jones, Daniel T.; Roos, Daniel (New York : HarperPerennial, 1991)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: auto-industrie; economische expansie; Japan